Republic of Niger : Trends of Poverty, Inequality, and Growth, 2005-2011 - World Bank (Washington, DC, 2015)
The ability to accurately monitor poverty trends is crucial to ensure the adoption of effective antipoverty policies and to assess progress toward the achievement of national development goals. In Niger, efforts to assess poverty dynamics between 2005 and 2011 are complicated by methodological differences in the three household surveys conducted over the period, in 2005, 2007-08 and 2011. While Niger’s overall poverty rate has dropped significantly between 2005 and 2011, changes in the poverty incidence are highly uneven across location types. Among the major causes of persistent poverty are the country’s minimal economic diversification and extremely limited agricultural infrastructure, which leave the majority of Nigerien households dependent on highly vulnerable farming and livestock production. In addition, the country’s extremely high rate of population growth presents a serious obstacle to sustainable poverty reduction. Not only does Niger have one of the highest population growth rates in the world, but fertility correlates inversely with income level. In other words, the fastest-growing segments of the population are also the poorest, and as a result, the declining trend in the national poverty rate is continuously offset by a steady increase in the absolute number of Nigeriens living in poverty. In addition, the relationship between population growth and rural-urban migration has important implications for poverty trends. Urban fertility rates are lower than rural rates and have been declining over time, while rural fertility rates remain both extremely high and relatively stable. Over the long run urbanization may have the added benefit of slowing nationwide population growth. However, this dynamic will be greatly accelerated by an independent improvement in conditions associated with lower birth rates in rural areas, including sustained increases in household incomes, broad improvements in education indicators, especially among women, and expanded access to healthcare facilities and family planning services.